Comparison of stress distribution around all-on-four implants of different angulations and zygoma implants: a 7-model finite element analysis - Hüseyin Alican Tezerişener; Öznur Özalp; Mehmet Ali Altay; Alper Sindel (BMC, 2024)
Abstract Background In recent years, zygomatic implants and the all-on-four treatment concept have been increasingly preferred for rehabilitation of atrophic maxillae. However, debate continues regarding the optimal configuration and angulation of the implants. The aim of this study was to analyze the biomechanical stress in implants and peri-implant bone in an edentulous maxilla with zygomatic implants and the all-on-four concept, using multiple implant configurations. Methods A total of 7 models consisting different combinations of 4-tilted dental implants and zygomatic implants were included in the study. In each model, a total of 200 N perpendicular to the posterior teeth and 50 N with 45° to the lateral tooth were applied. A finite element analysis was performed for determination of stress distribution on implants and peri-implant bone for each model. Results Higher stress values were observed in both cortical and trabecular bone around the 45°-tilted posterior implants in all-on-four models when compared to zygomatic implants. In cortical bone, the highest stress was established in an all-on-four model including 45°-tilted posterior implant with 4,346 megapascal (MPa), while the lowest stress was determined in the model including anterior dental implant combined with zygomatic implants with 0.817 MPa. In trabecular bone, the highest stress was determined in an all-on-four model including 30°-tilted posterior implant with 0.872 MPa while the lowest stress was observed in quad-zygoma model with 0.119 MPa. Regarding von Mises values, the highest stress among anterior implants was observed in an all-on-four model including 17° buccally tilted anterior implant with 38.141 MPa, while the lowest was in the including anterior dental implant combined with zygomatic implants with 20,446 MPa. Among posterior implants, the highest von Mises value was observed in the all-on-four model including 30°-tilted posterior implant with 97.002 MPa and the lowest stress was in quad zygoma model with 35.802 MPa. Conclusions Within the limits of the present study, the use of zygoma implants may provide benefit in decreasing biomechanical stress around both dental and zygoma implants. Regarding the all-on-four concept, a 17° buccal angulation of anterior implants may not cause a significant stress increase while tilting the posterior implant from 30° to 45° may cause an increase in the stress around these implants.